2014
DOI: 10.1007/s11999-014-3499-8
|View full text |Cite
|
Sign up to set email alerts
|

Minimally Invasive Versus Open Sacroiliac Joint Fusion: Are They Similarly Safe and Effective?

Abstract: Level III, therapeutic study. See Instructions for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
83
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(86 citation statements)
references
References 23 publications
3
83
0
Order By: Relevance
“…However, the number of patients reaching the minimally clinically important difference and those showing overall improvement were greater in the minimally invasive surgery group. The same author recently have published another paper [31] with 63 patients prospectively studied (open: 36; MIS: 27) who underwent SI joint fusion with minimum 1-year follow-up. Their results have shown that patients in the open group had a higher mean estimated blood loss (681 ml versus 41 ml, p<0.001).…”
Section: Discussionmentioning
confidence: 99%
“…However, the number of patients reaching the minimally clinically important difference and those showing overall improvement were greater in the minimally invasive surgery group. The same author recently have published another paper [31] with 63 patients prospectively studied (open: 36; MIS: 27) who underwent SI joint fusion with minimum 1-year follow-up. Their results have shown that patients in the open group had a higher mean estimated blood loss (681 ml versus 41 ml, p<0.001).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, minimally invasive techniques [21], which can also be performed percutaneously [22], were developed to reduce postoperative morbidity while maintaining or improving upon effectiveness. Some comparative studies suggest that minimally invasive strategies may be superior to open strategies [23][24][25]. Herein, we present the first prospective multicenter European study comparing the safety and effectiveness of minimally invasive SIJF using triangular titanium implants vs CM for patients with chronic SIJ pain.…”
Section: Introductionmentioning
confidence: 99%
“…Literature is scarce when it comes to describing the efficacy of surgical intervention, 22 and the general consensus is to refrain from surgery until all nonoperative treatment modalities have been exhausted. 1,2,5,12,14,15,19,22,25 Conservative methods for managing SIJ pain include trials of physical therapy, focusing on core and pelvic stability, external orthotics, pain management, periodic intra-articular injections, anti-inflammatory medications, and life style changes including smoking cessation and weight loss. 9,22 Whether efficacy is determined by objective measures, CT-confirmed fusion, or subjective methods, patients' levels of satisfaction with the results of fusion procedures are inconsistent.…”
Section: Discussionmentioning
confidence: 99%
“…The Smith-Petersen technique uses an iliac autograft fixated within the SIJ with atlanto-occipital screws. 4,19 Other techniques described in our literature search are a midline posterior approach us- ing pedicle screws and an autograft, or Cloward instrumentation; 2,4,10,12,14 an anterior approach with 3-hole plate and autograft; 15 and a bilateral Buttress with autograft 21 (Table 1). The MIS procedures included use of hollow modular anchorage screws, autograft, and bone morphogenetic protein (BMP), 1,13 longitudinally threaded cages with BMP, 25 multiple long screws crossing both SIJs engaging the iliac bones, 18 and the iFuse Implant System (SI-BONE) 7,9,15,19,20 ( Table 2).…”
Section: 14mentioning
confidence: 99%
See 1 more Smart Citation